POLYMORPHISM OF METHYLENETETRAHYDROFOLATE REDUCTASE (A1298C) AS A RISK FACTOR FOR OSTEOPOROSIS IN POST-MENOPAUSAL INDONESIAN WOMEN - Auerkari, Elza Ibrahim; Kusdhany, Lindawati; Umami, Sri Sofiati; Rahardjo, Tri Budi Wahyuni; Talbot, Christopher (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The study aimed to assess the association between the A1298C polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene and risk to osteoporosis in post-menopausal Indonesian women. Methods: After ethical approval, calcaneus bone mineral density (BMD) (T-scoring) was assessed from 194 consenting post-menopausal Indonesian women by dual-energy X-ray absorptiometry, and DNA of the participants was isolated from peripheral blood samples. To determine the status of A1298C polymorphism of MTHFR, isolated DNA was polymerase chain reaction (PCR) amplified in 35 cycles, to result in PCR product sizes of 302 bp (1298A) and 275 bp (1298C). For fragment detection, the PCR product was subjected to electrophoresis on agarose gel. The results were statistically assessed for genotype and allotype comparison according to the T-score grouping by Chi-square analysis, assuming statistical significance at p<0.05. Results: The results show no significant association between the T-score (BMD) grouping and genotype (or allotype) of the tested polymorphism of MTHFR. The observed genotype distribution of the tested MTHFR polymorphism (A1298C) differs clearly from those previously reported, with AC as the dominant genotype in the Indonesian sample population of the present work. Conclusion: The MTHFR (A1298C) polymorphism is relatively infrequent in the Indonesian female population, and no significant association was observed between this polymorphism, bone mineral density, and osteoporotic status.